2017
DOI: 10.1002/hbm.23812
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based source modeling of nociceptive cortical responses: A direct comparison of scalp and intracranial activity in humans

Abstract: Multiple overlapping activities evoked by nociceptive input can be disentangled from high-density scalp EEG guided by intracranial data. Modeled sources accurately described the timing and morphology of most activities recorded with intracranial electrodes, including those coinciding with the emergence of stimulus awareness. Hum Brain Mapp 38:6083-6095, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…Such significant changes of electrophysiological global network measures have been observed in different neurological and psychiatric disorders such as Alzheimer's disease (Stam, Jones, Nolte, Breakspear, & Scheltens, 2007;Yu et al, 2017), multiple sclerosis, and epilepsy (Stam, 2014). Although such changes have not directly been shown in chronic pain so far, fMRI studies reporting a global reorganization of the brain in chronic pain (Mano et al, 2018;Mansour et al, 2016) [Bradley et al, 2017]). T-maps of the seed-based connectivity contrasts between pain and control conditions are depicted (left and right side).…”
Section: Discussionmentioning
confidence: 98%
“…Such significant changes of electrophysiological global network measures have been observed in different neurological and psychiatric disorders such as Alzheimer's disease (Stam, Jones, Nolte, Breakspear, & Scheltens, 2007;Yu et al, 2017), multiple sclerosis, and epilepsy (Stam, 2014). Although such changes have not directly been shown in chronic pain so far, fMRI studies reporting a global reorganization of the brain in chronic pain (Mano et al, 2018;Mansour et al, 2016) [Bradley et al, 2017]). T-maps of the seed-based connectivity contrasts between pain and control conditions are depicted (left and right side).…”
Section: Discussionmentioning
confidence: 98%
“…Average delay between S1 and S2 in cats was 13 ms 30 , and mean latencies to activate area 17 from areas 18 and 19 were 6.1 and 10.4 ms respectively 31 . In humans, inter-hemispheric transmission between homologous S2 areas was reported to be of ~15 ms 32 , 33 , and direct electrical stimulation in epileptic patients estimated conduction times between insula and amygdala at 28 ± 3 ms 34 . Despite substantial variation of individual results around these averages 30 , 35 , published latency histograms show that 40–60% of cortico-cortical connections have latencies less than 10 ms 30 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that the N1 wave is particularly involved in translating noxious stimuli into motor and autonomic responses. The N1 mostly originates from primary sensorimotor cortex 23 with additional contributions from operculo-insular and midcingulate/supplementary motor cortices 24 . It reflects an early processing stage, which occurs regardless of whether a noxious stimulus is consciously perceived 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a role of N2 and P2 waves in translating noxious stimuli into pain perception is in line with recent functional magnetic resonance imaging (fMRI) studies 15 , 17 . These studies have shown that BOLD responses from cingulate and operculo-insular cortices 5 , 24 , which are the main generators of the N2 and P2 waves are involved in translating noxious stimuli into pain perception. Most recent evidence has extended that view by revealing a particularly close link between the N2 and P2 waves, salience, and motor responses 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%